Need Analysis of STEM-ESD Based Development on Teaching Materials and Instrument Test - Putri Amelia Solihah Solihah; Ida Kaniawati; Achmad Samsudin; Riandi Riandi (Jurnal Penelitian Pendidikan IPA, 2024)
This study aims to determine the need for developing STEM-ESD-based teaching materials as a learning resource for students in physics subjects in high school. This research uses mixed methods, which consisted of qualitative data and quantitative data. This research involved 26 respondents spread across several schools in Majalengka The instruments used are 17 questionnaires, namely 8 questions to identify difficulties in solving physics problems, 7 questions about student responses to the teaching materials used and 2 questions about causal factors and expected textbooks. Based on the preliminary study conducted, it is known that the teaching materials used so far have not met the indicators of good teaching materials, students have difficulty solving physics problems with a percentage of 73%, the student responses to the teaching materials used with a percentage of 81%, so require STEM-ESD-based teaching materials as a resource study. The results of the preliminary study also see that the teaching materials developed later can measure critical thinking and problem-solving skills. Based on this, the use of teaching materials as a learning resource is needed by students, so it is necessary to conduct a needs analysis in the development of STEM-ESD-based teaching materials